2022
DOI: 10.3390/pathogens11080867
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Features of SARS-CoV-2 in Extrapulmonary Organ Infection: A Systematic Review of Literature

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a global health concern responsible for the ongoing pandemic. Histopathological pieces of evidence on COVID-19 are not fully investigated. This review aims to provide, through microscopy investigations, a histopathological overview of COVID-19 structural and ultrastructural alterations in different organs and tissues, excluding the respiratory system. The authors systematically reviewed the literature over the period February 2020–July 2022. Selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 72 publications
2
31
0
Order By: Relevance
“…The hypoxia of respiratory distress syndrome can result in the continuous generation of reactive oxygen species and various pro-inflammatory factors to induce liver damage [ 28 ]. Other potential mechanisms of liver injury in hypoxia include hepatic venous congestion secondary to elevated central venous pressure, hypoxia reperfusion injury, high positive end-respiratory pressure (PEEP) use in intubated patients and vascular alterations [ 3 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hypoxia of respiratory distress syndrome can result in the continuous generation of reactive oxygen species and various pro-inflammatory factors to induce liver damage [ 28 ]. Other potential mechanisms of liver injury in hypoxia include hepatic venous congestion secondary to elevated central venous pressure, hypoxia reperfusion injury, high positive end-respiratory pressure (PEEP) use in intubated patients and vascular alterations [ 3 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous reports of endomyocardial biopsies taken from COVID-19-positive patients, SARS-CoV-2 viral particles will stay in the myocardial interstitial cells but not in cardiomyocytes or endothelial cells and alter the circulating lymphocytes and the immune system causing inflammation of the interstitial tissue evidenced by leukocyte infiltration and presence of CD4+ T cells indicating indirect injury to the cells by the virus [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“… 113 However, another up to date systematic review does show the presence of myocarditis, albeit infrequently, in available reported cases. 114 Current estimated rates of COVID-19 myocarditis are between 2.4 and 4.1 out of 1000 patients hospitalized for COIVD-19. 115 …”
Section: Heart Failure and Myocarditismentioning
confidence: 99%